Design of a Dual‐Responsive Bilayered Actuator with Alternating Active Layers. Issue 10 (2nd August 2022) - Zhou, Xiaohui; Feng, Chunmei; Li, Yuqi; Zhang, Shiping; Song, Botao
Abstract: Inspired by biological deformation in nature, numerous efforts have been made on the fabrication of biomimetic actuators, and the most facile way is to endow a bilayered structure with one active layer and the other inert layer. Unfortunately, such actuators can generally achieve single‐stimulus response and small deformation due to only one active layer. Here, a polyvinyl alcohol (PVA)/polystyrene (PS) bilayered actuator with alternating active layers for realizing dual‐responsiveness and large deformation is designed and assembled. Basically, upon stimulation by humidity, the hydrophilic PVA layer acts as an active layer due to its excellent water affinity, while the strong hydrophobic PS layer is an inert layer, and the unmatched swelling of the two layers results in bending deformation. While when exposed to an organic vapor environment, the roles of the two layers are interchanged and the PS layer is switched to be active, leading to fast organic vapor‐triggered deformation. The effects of relative humidity, types of organic vapor, sizes of the actuator, thickness ratios of the two layers, and cutting angles on shape deformation are systematically investigated. The underlying mechanisms of dual‐responsive shape deformation are further clarified. Potential applications of the bilayered actuator are finally demonstrated. Abstract : A bilayered actuator with alternating active layers is designed and fabricated. The bilayered actuator shows unique deformation under humidity stimulation. The bilayered actuator can bend after exposure to organic vapor environment.